2013
DOI: 10.1093/cvr/cvt140
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection in the aging, diabetic heart: the loss of protective Akt signalling

Abstract: An increased susceptibility to IRI in the aged, diabetic heart could be a consequence of impaired Akt signalling due to chronic Akt phosphorylation. Additional Akt phosphorylation required for IPC protection may therefore not be possible in the aged, diabetic rat heart and may explain why this cardioprotective manoeuvre cannot be achieved in these hearts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
4
73
2
2
Order By: Relevance
“…As IGF1R-PI3K-Akt signalling has also been shown to increase HSP70 in the heart 19,43 , we generated HF þ AF mice with IGF1R overexpressed and HSP70 deleted to confirm that IGF1R could also mediate protection independently of HSP70, as observed for BGP-15. The demonstration that both BGP-15 or increased IGF1R was capable of providing protection in the HF þ AF model, independent of the PI3K-Akt pathway and HSP70, is important because signalling via PI3K, Akt and HSP70 is often defective in the aged and/or diseased heart [44][45][46][47] . Previous studies have illustrated that increased IGF1/IGF1R is beneficial in multiple settings of cardiac pathology including DCM, hypertrophic cardiomyopathy (induced by pressure overload) and myocardial infarction 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As IGF1R-PI3K-Akt signalling has also been shown to increase HSP70 in the heart 19,43 , we generated HF þ AF mice with IGF1R overexpressed and HSP70 deleted to confirm that IGF1R could also mediate protection independently of HSP70, as observed for BGP-15. The demonstration that both BGP-15 or increased IGF1R was capable of providing protection in the HF þ AF model, independent of the PI3K-Akt pathway and HSP70, is important because signalling via PI3K, Akt and HSP70 is often defective in the aged and/or diseased heart [44][45][46][47] . Previous studies have illustrated that increased IGF1/IGF1R is beneficial in multiple settings of cardiac pathology including DCM, hypertrophic cardiomyopathy (induced by pressure overload) and myocardial infarction 48 .…”
Section: Discussionmentioning
confidence: 99%
“…In neonatal rat cardiac myocytes, IGF1 had an impact on potassium currents that protected myocytes against arrhythmogenesis, and this protection was mediated by both PI3K-dependent and PI3K-independent mechanisms 49 . Identification of drugs that can mediate protection independently of PI3K is of further significance because risk factors for HF and AF including obesity and diabetes have also been associated with impaired PI3K-Akt signalling in the heart [23][24][25]44 . Thus, a therapy that can provide protection independent of PI3K has the potential to be valuable in a number of settings.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental studies have also shown that the cardioprotective efficacy of pharmacologic preconditioning using a variety of different agents, including erythropoietin (Miki et al, 2009;Hotta et al, 2010), d-opioid receptor agonist (Hotta et al, 2010), isoflurane (Matsumoto et al, 2009), L-glutamate (Povlsen et al, 2009), remifentanil , and helium (Huhn et al, 2009b), is also impaired in the diabetic heart. Whittington et al (2013b) investigated the combined effect of diabetes and age on the response of the heart to acute ischemia/ reperfusion injury. As expected, the combination of aging (up to 18 months in the rat) and diabetes (Goto-Kaziaki rat) increased infarct size in response to acute ischemia/reperfusion and raised the threshold for ischemic preconditioning in a predictably additive manner.…”
Section: Diabetesmentioning
confidence: 99%
“…AMPK also facilitates the activation of silent information regulator 1 (SIRT1), which further increases PGC-1α transcriptional activity (Canto et al, 2009;Jiang et al, 2017;Liang et al, 2017). Conversely, PGC-1α activity can be inhibited by Akt-mediated phosphorylation (Whittington et al, 2013). The underlying mechanisms may involve the direct phosphorylation of PGC-1α by Akt, which prevents the recruitment of PGC-1α to its cognate promoter regions .…”
Section: Regulation Of Pgc-1mentioning
confidence: 99%